The Virtual Rebirth of Paganism - Bainbridge, William Sims (Journal for religion, film and media, 2023)
A quarter millennium ago, monarchies began to vanish from the Earth, and some utopian computer games implicitly explore how that might also happen in Heaven, through the resurrection of many competing gods. This essay begins by examining how two very popular massively multiplayer online games, DARK AGE OF CAMELOT and AGE OF CONAN, manage complex social and cultural structures. Both combine real history with legends, the first including the Norse pantheon of gods and the second emphasizing the Egyptian serpent deity, Set. They offer different degrees of fantasy and of conflict between three primary factions of players, each represented as a culture or coalition of cultures. With that background, a series of diverse examples will suggest a variety of ways in which computer games and virtual worlds are exploring the modern meanings of ancient religions that were replaced by monotheism. The concluding section examines in closer detail the connections between religion and aspects of everyday life of virtual ancient Egyptians, in A TALE IN THE DESERT. Post-modern gaming culture endorses tribalism, enjoys imagining the collapse of civilization, and seeks escape from traditional faith, possibly even from any coherent philosophy of ethics. However, this is a form of idealism rather than criminality, imagining the rebirth of creative legends and total religious freedom, often through the metaphor of repaganization.